2014
DOI: 10.1002/2013sw001014
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the thermosphere as a driven-dissipative thermodynamic system

Abstract: Thermospheric density impacts satellite position and lifetime through atmospheric drag.More accurate specification of thermospheric temperature, a key input to current models such as the High Accuracy Satellite Drag Model, can decrease model density errors. This paper improves the model of Burke et al. (2009) to model thermospheric temperatures using the magnetospheric convective electric field as a driver. In better alignment with Air Force satellite tracking operations, we model the arithmetic mean temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…They found that in the weaker events, the contributions of Joule heating and EPP are roughly equal, whereas in strong events, Joule heating dominates. Several papers (Burke et al, 2009(Burke et al, , 2010Burke, 2011;Frey et al, 2014) have studied the density response to solar wind variations by treating the thermosphere empirically as a dissipative system, using exospheric temperature inferred from accelerometer measurements. Weimer et al (2011) related Poynting flux derived from interplanetary magnetic field (IMF) measurements to exospheric temperature derived from CHAMP and GRACE, for possible use as a geomagnetic activity argument in empirical models.…”
Section: Geomagnetic Activity Responsementioning
confidence: 99%
See 1 more Smart Citation
“…They found that in the weaker events, the contributions of Joule heating and EPP are roughly equal, whereas in strong events, Joule heating dominates. Several papers (Burke et al, 2009(Burke et al, , 2010Burke, 2011;Frey et al, 2014) have studied the density response to solar wind variations by treating the thermosphere empirically as a dissipative system, using exospheric temperature inferred from accelerometer measurements. Weimer et al (2011) related Poynting flux derived from interplanetary magnetic field (IMF) measurements to exospheric temperature derived from CHAMP and GRACE, for possible use as a geomagnetic activity argument in empirical models.…”
Section: Geomagnetic Activity Responsementioning
confidence: 99%
“…They proposed that the latter component could be used as a proxy for the response of the thermosphere to geomagnetic activity forcing. Several papers (Burke et al, 2009(Burke et al, , 2010Burke, 2011;Frey et al, 2014) have examined the density response to solar wind variations by treating the thermosphere empirically as a dissipative system, using exospheric temperature inferred from accelerometer measurements. Bhatnagar et al (2005) examined storm-induced variations in orbit-derived density near 200 km altitude during 2001.…”
Section: Time-dependent Response To the Solar Wind And Imfmentioning
confidence: 99%
“…Bussy‐Virat et al () reports that the largest source of errors for LEO satellite orbit determination comes from the thermospheric neutral density, which is largely enhanced by the JH during the geomagnetic storms (Zesta & Huang, ). JH causes the upwelling of the neutrals in the thermosphere resulting in the enhanced atmospheric drag on the satellites, thus becomes one of the main contributors in the drag force through the variations in thermospheric neutral density (Fedrizzi et al, ; Frey et al, ). Larger atmospheric drag reduces the life time of the satellites and increases orbit prediction errors and the probability of collisions between the objects existing in the LEO (Prölss, ; Zesta & Huang, ).…”
Section: Introductionmentioning
confidence: 99%